2009
DOI: 10.2214/ajr.09.3599
|View full text |Cite
|
Sign up to set email alerts
|

Chest Radiographic and CT Findings in Novel Swine-Origin Influenza A (H1N1) Virus (S-OIV) Infection

Abstract: Chest radiographs are normal in more than half of patients with S-OIV (H1N1) and progress to bilateral extensive air-space disease in severely ill patients, who are at a high risk for PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
180
15
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(241 citation statements)
references
References 6 publications
31
180
15
15
Order By: Relevance
“…However, more severe cases may develop particularly in the patients at high risk. As in our study, it has been reported that pandemic influenza A (H1N1) is also able to cause severe cases such as pneumonia and ARDS [1,6,8,9]. Clinically, there may be fever, dry cough, headache, sore throat, cold feeling, fatigue, malaise, muscle and joint pain, vomiting, nasal drainage, and diarrhea [4].…”
supporting
confidence: 57%
“…However, more severe cases may develop particularly in the patients at high risk. As in our study, it has been reported that pandemic influenza A (H1N1) is also able to cause severe cases such as pneumonia and ARDS [1,6,8,9]. Clinically, there may be fever, dry cough, headache, sore throat, cold feeling, fatigue, malaise, muscle and joint pain, vomiting, nasal drainage, and diarrhea [4].…”
supporting
confidence: 57%
“…Even in combination with optimal supportive care, therapy with antiviral drugs does not completely prevent mortality (8), indicating that new therapeutic approaches are needed. Given reports that microthombi are observed in the lungs of patients with severe influenza (10,19) and that platelet inhibition ameliorates certain forms of lung injury (14,15), we hypothesized that the influenza virus induces platelet adhesion to the lung endothelium and that this process contributes to the pathology of severe influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the endothelium normally is antithrombogenic and prevents platelet adhesion. An effect of the virus to induce platelet-endothelial adhesion is plausible: numerous reports describe pulmonary thrombi as an important complication of severe infections with influenza (10,19), while endothelial activation, which would be expected to induce platelet adhesion, was highly correlated with death from influenza in a murine model (20). Furthermore, a study of patients with venous thromboembolism found that vaccination against influenza was associated with a protective effect against pulmonary clots (21).…”
mentioning
confidence: 99%
“…Lung consolidation and infiltrates with or without pleural effusion were the two plain film patterns found in chest radiographies in our patients. The possibility of an under‐diagnosis of pulmonary embolism and pneumo‐mediastinum that had previously been observed in patients with pandemic influenza A (H1N1) could not be excluded, 36 as our patients were evaluated by plain chest radiographs which were less sensitive in the detection of such abnormalities than a computed tomography 37 …”
Section: Discussionmentioning
confidence: 99%